Fruit Industry - Kahramanoğlu, İbrahim; Wan, Chunpeng (IntechOpen, 2022)
Fruits contain important vitamins, minerals, phytochemical compounds, and dietary fiber. The phytochemicals in fruit can reduce the risk of diseases such as cancer, heart disease, diabetes, and hypertension. Fruits play an important role in not only human health but also in the world economy. As the global population continues to grow, there is an urgent need to ensure all people have access to healthy foods, thus the fruit industry is integral to ensuring food security and sustainability. This book provides a comprehensive overview of the fruit industry and highlights new topics for future research.